Soil column leaching experiments – inverse modelling to derive environmental fate parameters - Stephan Sittig; Thomas Augustin; Siqi Cao; Robin Sur (Environmental Advances)
For substances with very low sorption in the OECD study 106, a column leaching study according to OECD Guideline 312 is recommended. However, the method to evaluate these experiments is often not applicable due to breakthrough of the solute. Therefore, we suggest a new evaluation procedure by inverse modelling with HYDRUS-1D and PEST. Using an example substance as a case study, not only the final concentration profiles in the column were considered but also the breakthrough curves. The distribution coefficients between the liquid and the organic matter in the solid phase were determined with soil-pH dependent results in the range of 0.29 L/kg – 286 L/kg with reasonably small uncertainties. Comparison with a global solver (DREAM_ZS) corroborated the solutions. This procedure is suggested to determine sorption parameters for compounds currently not possible to evaluate in regulatory exposure assessments, considering numerical simulations and more robust parameter estimation including parameter uncertainties.